A Blended Physiotherapy Intervention for Persons With Hemophilic Arthropathy: Development Study - Timmer, Merel A (J Med Internet Res, 2020)
BACKGROUND: Joint bleeds are the hallmark of hemophilia, leading to a painful arthritic condition called as hemophilic arthropathy (HA). Exercise programs are frequently used to improve the physical functioning in persons with HA. As hemophilia is a rare disease, there are not many physiotherapists who are experienced in the field of hemophilia, and regular physiotherapy sessions with an experienced physiotherapist in the field of hemophilia are not feasible for persons with HA. Blended care is an innovative intervention that can support persons with HA at home to perform the advised physical activities and exercises and provide self-management information. OBJECTIVE: The aim of this study was to develop a blended physiotherapy intervention for persons with HA. METHODS: The blended physiotherapy intervention, namely, e-Exercise HA was developed by cocreation with physiotherapists, persons with HA, software developers, and researchers. The content of e-Exercise HA was compiled using the first 3 steps of the Center for eHealth Research roadmap model (ie, contextual inquiry, value specification, and design), including people with experience in the development of previous blended physiotherapy interventions, a literature search, and focus groups. RESULTS: A 12-week blended intervention was developed, integrating face-to-face physiotherapy sessions with a web-based app. The intervention consists of information modules for persons with HA and information modules for physiotherapists, a graded activity program using a self-chosen activity, and personalized video-supported exercises. The information modules consist of text blocks, videos, and reflective questions. The patients can receive pop-ups as reminders and give feedback on the performance of the prescribed activities. CONCLUSIONS: In this study, we developed a blended physiotherapy intervention for persons with HA, which consists of information modules, a graded activity program, and personalized video-supported exercises.